PENERAPAN MEDIA PEMBELAJARAN SCRAPBOOK UNTUK MENINGKATKAN KREATIVITAS BELAJAR SISWA KELAS XI FASE 2 SMA NEGERI 4 MERANGIN - Muhamad Aldian Roni; Ervan Johan Wicaksana; Yoan Mareta (Prabayaksa: Journal of History Education, 2025)
This study aims to describe the increase in students learning creativity through the application of scrapbook learning media based on historical material under Japanese tyranny in history subjects at SMA Negeri 4 Merangin. This study uses Classroom Action Research techniques. The variables studied include the increase in learning creativity that was successfully achieved by students after two cycles of learning, where one cycle consists of four stages, namely planning, action, observation, and reflection. The results of the study showed that there was an increase in learning creativity in class XI Phase 2 students of SMA Negeri 4 Merangin when learning using scrapbook learning media. In cycle I, action 1 had an average value of learning creativity of 54% with 4 people in the creative category, while action 2 was 61% with 12 people in the creative category. In cycle II action 3 the average value of stundents leraning creativity increased by 66% with 20 people in the creative category. While action 4 was 78% with 14 people in the very creative category and 18 people in the creative category. These result exceeded the set completion criteria which was 70%.